Heart failure medication use and follow-up patterns in renal transplant recipients with reduced ejection fraction: A single-center experience - Michael C. Hill; Kaitlyn Legg; Amer Ardati; Vicki Groo (International Journal of Cardiology: Heart & Vasculature)
Background: The role of medical therapy for heart failure with reduced ejection fraction (HFrEF) in subjects with end-stage renal disease receiving renal transplantation (RT) is understudied. Here, we describe post-RT HFrEF medical management practices at a single urban, academic tertiary care center. Methods: RT recipients between January 1, 2015 and November 30, 2020 with history of ejection fraction (EF) <40 % prior to RT were included. Medications, renal function, blood pressure, cardiology follow-up, and echocardiograms ≥90d post-RT were retrospectively collected for 2 years post-RT. Results and conclusions: 47/750 (6.3 %) of RT recipients had prior HFrEF diagnosis, of whom 26 experienced improvement in EF prior to RT. Pre-RT medical therapy included beta blocker (BB) in 43 (92 %) of subjects and renin-angiotensin-aldosterone inhibitors (RAASi) in 23 (49 %). By 24 months post-RT, BB were used in 34 (76 %) and RAASi were used in 12 (27 %) of subjects. Rates of post-RT cardiology follow-up (51 %) and echocardiogram (38 %) were lower than expected in this cohort. Of 29 subjects potentially eligible for RAASi based on preserved renal function and no hyperkalemia or hypotension episodes during follow-up, only 6 (21 %) received RAASi. Of 6 subjects with post-RT EF <50 %, 4 were eligible but did not receive RAASi. Multidisciplinary collaboration between cardiology and transplant teams may help improve care for this high-risk patient population.